Transformasi Ekonomi Ibu Rumah Tangga melalui Inkubasi Bisnis Online Berbasis Komunitas - Annisaturrahmi, Annisaturrahmi (Yayasan Pendidikan Mitra Mandiri Aceh(YPMMA), 2023)
The role of housewives in family economics is often overlooked, despite their significant potential to improve household welfare, especially in the digital era. This article aims to present the results of a community service program in the form of a community-based online business incubation designed to empower housewives. The study employed a qualitative approach using a case study method involving 15 participants. Data were collected through participatory observation, in-depth interviews, focus group discussions (FGDs), and documentation. The results show a significant increase in digital knowledge and skills, the establishment of new online businesses, increased family income, the formation of supportive communities, and the growth of self-confidence and economic independence among participants. These findings confirm that a community-based approach, structured training, and intensive mentoring can serve as catalysts for the economic transformation of housewives. However, challenges such as limited capital, time management, and internet access remain critical issues that need to be addressed in the future development of similar programs.